2009
DOI: 10.1371/journal.ppat.1000280
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus NSP1 Inhibits NFκB Activation by Inducing Proteasome-Dependent Degradation of β-TrCP: A Novel Mechanism of IFN Antagonism

Abstract: Mechanisms by which viruses counter innate host defense responses generally involve inhibition of one or more components of the interferon (IFN) system. Multiple steps in the induction and amplification of IFN signaling are targeted for inhibition by viral proteins, and many of the IFN antagonists have direct or indirect effects on activation of latent cytoplasmic transcription factors. Rotavirus nonstructural protein NSP1 blocks transcription of type I IFNα/β by inducing proteasome-dependent degradation of IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
176
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(190 citation statements)
references
References 65 publications
(87 reference statements)
11
176
0
2
Order By: Relevance
“…Adenovirus E1A protein inhibits TNF-a-induced NF-kB activation through suppression of IKK activity and IkBa phosphorylation (36). Rotavirus NSP1 inhibits NF-kB activation by inducing proteasomedependent degradation of b-transducin repeat-containing protein (37,38). In the current study, we report that EV71 2C protein can directly interact with IKKb by inhibiting IKKb activation and IkBa phosphorylation/degradation, and thus inhibits TNF-ainduced NF-kB activation.…”
Section: Discussionsupporting
confidence: 48%
“…Adenovirus E1A protein inhibits TNF-a-induced NF-kB activation through suppression of IKK activity and IkBa phosphorylation (36). Rotavirus NSP1 inhibits NF-kB activation by inducing proteasomedependent degradation of b-transducin repeat-containing protein (37,38). In the current study, we report that EV71 2C protein can directly interact with IKKb by inhibiting IKKb activation and IkBa phosphorylation/degradation, and thus inhibits TNF-ainduced NF-kB activation.…”
Section: Discussionsupporting
confidence: 48%
“…The rotavirus gene segment encoding the nonstructural protein 1 (NSP1) is an important determinant of host restriction of viral replication both in vitro (17,53) and in vivo (9). Specifically, we along with others have reported a role for NSP1 in regulating the ability of rotavirus to efficiently cause diarrhea in mice (9), spread from animal to animal (9), replicate in vivo and in vitro (4,(15)(16)(17), and antagonize IFN (4,5,17,24,25,53). Thus, the host innate immune response is an important determinant of rotavirus host range restriction and depends on both the virus strain and host cell or tissue type.…”
Section: In Mouse Embryonic Fibroblasts (Mefs) the Bovine Rotavirusmentioning
confidence: 85%
“…At least two distinct mechanisms by which rotaviruses inhibit the host IFN response have been reported: (i) NSP1-mediated proteasomal degradation of host transcription factors IRF3 and IRF7, resulting in diminished IFN-␤ gene transcription and antiviral activity (4,5), and (ii) proteasomal degradation of ␤-TrCP, leading to inhibition of NF-B activity and subsequent IFN-␤ gene transcription (24). In contrast to these examples, we reported that the UK bovine rotavirus strain was unable to block IFN-␤ secretion in murine fibroblasts (17), and this correlated with the lack of murine IRF3 degradation by UK NSP1 (53).…”
mentioning
confidence: 99%
“…Moreover, NSP1 seems to interact with the cellular transcription factor interferon regulatory factor 3 (IRF3) and targets it for degradation by the proteasome, thus acting to avoid the host antiviral defense by the blocking INF production [14][15][16][17][18] . However, NSP1 seems not to be necessary for rotavirus replication in vitro and its role is not fully clear 19 .…”
Section: Proteins Involved In Replication Pathogenesis and Immune Rementioning
confidence: 99%